Becoming What We Know: Franz von Baader on Cognition and Revelation - Björk, Mårten (Philosophy, theology and the sciences, 2024)
This essay examines the Bavarian physician, mining engineer, and Catholic romantic philosopher Franz von Baader's (1765-1841) enigmatic claim that we think because we are thought with the help of the moral theologian Servain Pinckaers OP (1925-2008) and the psychologist Mihaly Csikszentmihalyi (1934-2021). Using Pinckaers' idea of 'fontal knowledge' and Csikszentmihalyi's notion of flow, I interpret Baader's understanding of cognition as a theory of intuition and cognitive similitude. For Baader, cognition is a revelation of what is outside us and can be understood with theological terms such as intuition, faith, or trust. But he thinks that a fundamental anxiety inherent in human existence constantly threatens this cognitive trust to the point that we believe that thought begins egoistically and solipsistically with the self. What he describes with Jacob Böhme (1575-1624) as the potential agony for every living organism disrupts the flow of revelation that discloses that we cannot be if we have not been made, think if we have not been thought, love if we have not been loved. By challenging, or what Baader with his strange jargon calls abbreviating, this asocial but reflective disruption of our intuitive thinking through a cognitive flow where act and actor are merged, we reestablish our relation to that which precedes us and gives us being.